Pulmonary Pulse Wave Transit Time is Associated with Right Ventricular–Pulmonary Artery Coupling in Pulmonary Arterial Hypertension. (1st December 2016) - Prins, Kurt W.; Weir, E. Kenneth; Archer, Stephen L.; Markowitz, Jeremy; Rose, Lauren; Pritzker, Marc; Madlon‐Kay, Richard; Thenappan, Thenappan
Abstract : Pulmonary pulse wave transit time (pPTT), defined as the time for the systolic pressure pulse wave to travel from the pulmonary valve to the pulmonary veins, has been reported to be reduced in pulmonary arterial hypertension (PAH); however, the underlying mechanism of reduced pPTT is unknown. Here, we investigate the hypothesis that abbreviated pPTT in PAH results from impaired right ventricular–pulmonary artery (RV‐PA) coupling. We quantified pPTT using pulsed‐wave Doppler ultrasound from 10 healthy age‐ and sex‐matched controls and 36 patients with PAH. pPTT was reduced in patients with PAH compared with controls. Univariate analysis revealed the following significant predictors of reduced pPTT: age, right ventricular fractional area change (RV FAC), tricuspid annular plane excursion (TAPSE), pulmonary arterial pressures (PAP), diastolic pulmonary gradient, transpulmonary gradient, pulmonary vascular resistance, and RV‐PA coupling (defined as RV FAC/mean PAP or TAPSE/mean PAP). Although the correlations between pPTT and invasive markers of pulmonary vascular disease were modest, RV FAC ( r = 0.64, P < 0.0001), TAPSE ( r = 0.67, P < 0.0001), and RV‐PA coupling (RV FAC/mean PAP: r = 0.72, P < 0.0001; TAPSE/mean PAP: r = 0.74, P < 0.0001) had the strongest relationships with pPTT. On multivariable analysis, only RV FAC, TAPSE, and RV‐PA coupling were independent predictors of pPTT. We conclude that shortening of pPTT in patients with PAH results from altered RV‐PA coupling, probably occurring as a result of reduced pulmonary arterial compliance. Thus, pPTT allows noninvasive determination of the status of both the pulmonary vasculature and the response of the RV in patients with PAH, thereby allowing monitoring of disease progression and regression.